Թուրքիայի հարաբերությունները Մաղրիբի արաբական երկրների հետ 2002-2012թթ.-ին - Արմեն Ժամհարյան (ՀՀ ԳԱԱ հրատ.)
Relations between Turkey and the Arab Maghreb are rather close. This is evidenced by a formal diplomatic statements, made by the two sides in 2002-2012 , mutual visits, joint financial programs, etc. This fact is also evidenced by the fact, that during the Libyan war Turkey refused to take direct part in military operations, as well as provided a large amount of humanitarian, financial Many citizens of Turkey live and work in Maghreb Arabic countries, which is a result of strong economic and political ties between the two sides, and, in its turn, contributes to even closer relations between two sides . To the deepening of close relations with Turkey, contributes also the memory of common historical past, the impact of which one may feel even now, at the Turkish families by origin, in Maghreb Arabic countries, especially from Tunisia and Algeria.and other assistance to Libya.
Keywords: Political Science